The Role & Authority of Inner Notary Making of Heritage Actions - Muhammad Iqbal (Sultan Agung Notary Law Review, 2020)
This study aims to determine the Role and Authority of Notaries in Making the Inheritance Deed and to find out and analyze the obstacles and solutions by the Notary in making the Inheritance Deed. The data used in this study are primary data, secondary data and tertiary data that can support the assessment, which are then analyzed using descriptive analytical methods. Based on the results of data analysis, it can be concluded that: The notary's duty is to formulate the wishes and actions of the parties into an Authentic Deed with due regard to and not violating applicable legal provisions. Authentic Deed as a Deed that has perfect legal force of proof and is binding for the parties, so that the proof can stand alone and do not need to receive assistance and additional other evidence. If any opposing party can prove the Deed is not true with another Otentiuk Deed, then the level of proof of the Authentic Deed may decrease, so that additional evidence is needed. In the making of the inheritance deed, there are several things that are important in the making of the inheritance deed, such as, the parties do not agree, the heir is not legally competent.